PENCIPTAAN BUKU ILUSTRASI GAMELAN JAWA DENGAN MENGGUNAKAN TEKNIK VEKTOR SEBAGAI UPAYA PENGENALAN ALAT MUSIK TRADISIONAL PADA ANAK-ANAK - Rudiansyah, Afrizal; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: Gamelan is a traditional musical instrument that was in Indonesia, which has its own historical and artistic value. For the Javanese gamelan has become part of their life since the Hindu-Buddhist culture when it was still a lot of influence in Indonesia. Gamelan is a collection of various kinds of musical instruments consisting of drum / drums, Peking, Saron, Demung, Gong, Kempul, Bonang, kethuk, Kenong, Gender, Xylophone, fiddle, zither, flute. At the staging Puppet or Dance and Gamelan often be used as a musical accompaniment. In an effort to preserve and introduce traditional musical instruments to children, it will be the creation of Javanese gamelan book illustrations using vector techniques in an effort introduction of a traditional musical instrument in children. The method used is qualitative methods by conducting interviews, observation, documentation and literature to obtain the data used in the creation of book illustration traditional Javanese gamelan musical instruments. From analysis obtained then found the keyword